(untitled) (Research, Society and Development, 2021)
The use of different methods to control phytopathological diseases reduces the use of chemicals. The anthracnose disease causes several damages to the production of several plants, including the “dedo-de-moça” pepper (Capsicum baccatum) and can completely affect the fruits, making its trade unfeasible and causing great losses in production. Society has increasingly demanded quality food without pesticides, as it causes several damages to health. Therefore, the use of alternative means may be a viable option for small, medium and large producers. Therefore, the objective of this work was to analyze alternative methods for the control of the fungus Colletotrichum gloeosporioides, the causal agent of anthracnose disease through the application of different dosages of neem oil, clove essential oil and aqueous extract of hot chili pepper in vitro. The experimental design used was completely randomized (DIC) with 16 treatments and 10 repetitions in different concentrations, totaling 160 Petri dishes. The measurements of the mycelial growth of the pathogen were performed with the support of a digital caliper ruler on alternate days, totaling 6 days of observation. The results obtained revealed that the use of neem oil and clove essential oil in the minimum dosage (dilution 10-5) promoted a reduction in the mycelial growth of the pathogen C. gloeosporioides, with emphasis on the neem oil that was more efficient than clove essential oil. The aqueous extract of chili peppers did not show good results in inhibiting the mycelial growth of the pathogen when compared to the control.